2015
DOI: 10.1021/acs.jpca.5b06893
|View full text |Cite
|
Sign up to set email alerts
|

Valence Virtual Orbitals: An Unambiguous ab Initio Quantification of the LUMO Concept

Abstract: Many chemical concepts hinge on the notion of an orbital called the lowest unoccupied molecular orbital, or LUMO. This hypothetical orbital and the much more concrete highest occupied molecular orbital (HOMO) constitute the two "frontier orbitals", which rationalize a great deal of chemistry. A viable LUMO candidate should have a sensible energy value, a realistic shape with amplitude on those atoms where electron attachment or reduction or excitation processes occur, and often an antibonding correspondence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 155 publications
1
80
0
Order By: Relevance
“…Recent reports in the literature have shown the limitation of these Kohn–Sham orbitals, especially for those that are unoccupied. Therefore, these unoccupied orbitals are probably conceptually defective and have to be interpreted with very special care …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports in the literature have shown the limitation of these Kohn–Sham orbitals, especially for those that are unoccupied. Therefore, these unoccupied orbitals are probably conceptually defective and have to be interpreted with very special care …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these unoccupied orbitals are probably conceptually defective and have to be interpreted with very specialc are. [54,55] The NBO analysis revealed that donor-acceptor interactions within these complexes involve mainly the interaction of the lone pairs of the deprotonated Im nitrogen atom (N10) and Zn (i.e.,L P(1)N10;F igure 4). This is associated with intramolecular CT through the Im aromatic ring.…”
Section: Charget Ransfer Analysismentioning
confidence: 99%
“…The structural compatibility is crucial in any MOF where it helps the organic linker to absorb photon and creates a charge separated exciton, which was previously ligand localized via transfer of electron from Highest Occupied Molecular Orbital [HOMO] of the linker to the Lowest Unoccupied Molecular Orbital [LUMO] of the metal nods. [70] Generally, the HOMO-LUMO energy gap ranges from 1 to 5 eV places the MOF between semiconductor and insulator. [71] The promising semiconducting nature of MOF allows it to be used as electrode in photo electro chemical [PEC] devices that electrolyzes water by solar light illumination.…”
Section: Journey Of Mof As Photocatalystmentioning
confidence: 99%
“…Mulliken's and Lowdin's population analyses, Morokuma's energy decomposition analysis, Bader's “atom in molecules” analysis, and Weinhold's Natural Bond Orbital NBO analysis are widely used to characterize wavefunctions and the interactions within chemical systems. Recently Ruedenberg and coworkers have also developed the “quasi‐atomic orbital” QAO analysis that they have extended into an energy decomposition analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The MOA is related to the “intrinsic quasi‐atomic orbital” QAO analysis and also to the natural bond orbital NBO analysis . In QAO analysis the molecular orbitals are projected onto what are essentially complete or exact atomic orbitals.…”
Section: Introductionmentioning
confidence: 99%